2006
DOI: 10.1037/0021-9010.91.5.1013
|View full text |Cite
|
Sign up to set email alerts
|

Understanding attitudes toward affirmative action programs in employment: Summary and meta-analysis of 35 years of research.

Abstract: Affirmative action programs (AAPs) are controversial employment policies in the United States and elsewhere. A large body of evidence about attitudinal reactions to AAPs in employment has accumulated over 35 years: at least 126 independent samples involving 29,000 people. However, findings are not firmly established or integrated. In the current article, the authors summarize and meta-analytically estimate relationships of AAP attitudes with (a) structural features of such programs, (b) perceiver demographic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
401
3
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(430 citation statements)
references
References 123 publications
21
401
3
5
Order By: Relevance
“…Because we wished to motivate participants to take the selection task seriously, participants were told that in Phase 3 they would participate in a face-to-face group exercise with the people they selected to work with in Phase 2 and that the highest performing group in the laboratory exercise would receive a monetary reward ($100 for each of the four group members). However, Phase 2 was the last component of the study; none of the participants would 1 We choose to focus on job qualifications rather than implement preferential selection criteria because previous research demonstrated that job candidates as well as their coworkers react more positively to situations in which qualifications are explicitly used in selection decisions rather than ambiguous or preferential selection (Harrison, Kravitz, Mayer, Leslie, & Lev-Arey, 2006;Heilman, Battle, Keller, & Lee, 1998). Therefore, we sought to determine if a selection strategy (i.e., focusing on qualifications) that generates positive views from job candidates and coworkers would also lead to less discriminatory responses from those making selection decisions.…”
Section: Methodsmentioning
confidence: 99%
“…Because we wished to motivate participants to take the selection task seriously, participants were told that in Phase 3 they would participate in a face-to-face group exercise with the people they selected to work with in Phase 2 and that the highest performing group in the laboratory exercise would receive a monetary reward ($100 for each of the four group members). However, Phase 2 was the last component of the study; none of the participants would 1 We choose to focus on job qualifications rather than implement preferential selection criteria because previous research demonstrated that job candidates as well as their coworkers react more positively to situations in which qualifications are explicitly used in selection decisions rather than ambiguous or preferential selection (Harrison, Kravitz, Mayer, Leslie, & Lev-Arey, 2006;Heilman, Battle, Keller, & Lee, 1998). Therefore, we sought to determine if a selection strategy (i.e., focusing on qualifications) that generates positive views from job candidates and coworkers would also lead to less discriminatory responses from those making selection decisions.…”
Section: Methodsmentioning
confidence: 99%
“…Also, like any type of organizational change, implementing new diversity policies may cause resistance (Thomas and Plaut 2008). Harrison et al (2006) provide a meta-analysis showing how affirmative action programs, some of the most widely used diversity interventions, may have negative impact on majority members' acceptance of diversity. They also mention, however, that these effects may be reduced by the way diversity policies are communicated and justified within the organization.…”
Section: Importance Of Measuring Perceptions Towards Diversitymentioning
confidence: 99%
“…Jehn et al 1999;McLeod and Lobel 1992;Van Knippenberg et al 2004). However, successfully managing diversity appears to be difficult, as it is also associated with negative team outcomes (Jehn et al 1999;Mannix and Neale 2005;Van Knippenberg and Schippers 2007) and resistance among employees (Thomas and Plaut 2008;Harrison et al 2006;Antwi-Boasiako 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The strongest driver of intentions, for both managers and employees, was attitude towards cultural diversity management promotion. Attitudes are known to be relatively stable and difficult to change (Harrison et al, 2006). Organizations trying to build a cultural inclusive organization may want to focus on attitude, especially when selecting managers.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that individuals evaluated affirmative action more negatively when they perceived it as employing preferential treatment. Harrison et al (2006) conducted a meta-analysis of studies on attitudes towards affirmative action and showed that the fairer a practice was perceived to be, the more positively it was evaluated. This meta-analysis also revealed that ethnic minorities were more positive than ethnic majority group members towards affirmative action.…”
Section: Psychological Predictors Of Workplace Cultural Diversity Supmentioning
confidence: 99%